At the edge of sight : photography and the unseen - Smith, Shawn Michelle, 1965- (Duke University Press, 2013)
Shawn Michelle Smith examines how the advent of photography revolutionized perception, making what was once invisible visible, while also revealing the limitations of what can be seen.